Interaction between Children with Developmental Disabilities and Artwork - Brajčić, Marija; Sunko, Esmeralda (Revija za elementarno izobraževanje, 2020)
The study was conducted among students with developmental disabilities at three institutions in Split, Croatia. A total of 32 students a ged f rom 1 7 t o 21 participated in the study. A qualitative study employing the method of aesthetic transfer was conducted, aiming to encourage students to react, and to recognize differences between their reactions. The students communicated with the artworks of the modern painter Joan Miró. The research has shown that observing artworks as part of visual arts activity in institutions involving students with developmental disabilities fulfills its purpose, because a structured method for observing artwork served to self-activate students to assess their own competences and competences in visual arts expression.
Keywords: Joan Miró, method of aesthetic transfer, students with disabilities